International Collaboration Community Service Indonesia Banking School – Khon Kaen Business School: SIMPPRO (Sistem Manajemen Peningkatan Produktivitas) to Improve Productivity Level of SMEs in Indramayu, West Java, Indonesia - Ferli, Ossi; Andriani, Meta; Hariyanti, Enny; Budhijana, Bambang; Paulina, Paulina; Pracoyo, Antyo; Wardani, Deni; Rimadias, Santi; Wijaya, Erric; Setiawati, Asri; Noviyanti, Indah Salsa; Phimnoi, Kanokwan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Productivity is the most powerful driving force for a country's economic growth and business growth at the company level. Through international collaboration, community service activities were carried out by Indonesia Banking School, Jakarta, Indonesia, and Khon Kaen Business School, Khon Kaen, Thailand in educating in terms of assessing productivity improvement using SIMPPRO (Productivity Improvement Management System). The implementation was carried out within the Manpower Office of Indramayu Regency, West Java to realize a productivity improvement program. Participants were attended by 17 representatives from MSMEs, LPK, and other companies and 6 representatives from employees of the Indramayu Regency Manpower Office. The method of implementation is carried out in the form of training. The results of the evaluation of activities based on participants' answers through questionnaires, amounting to 93.68% on average gave Good and Very Good ratings.